Bridge-based remote sensing of NOx emissions from locomotives. (1st February 2019) - Breuer, Matthew A.; Burgard, Daniel A.
Abstract: While emissions from nonroad mobile sources, such as locomotives, have gained increased regulatory scrutiny, a surprisingly few number of real-world, in-use measurements exist. This paper reports the use of a Remote Sensing Device (RSD) to measure emissions from locomotives. This noninvasive technique measured NO and NO2 emissions from individually identified locomotives as their exhaust plumes passed through the sensing beam of the RSD on a bridge directly above the moving sources. NOx emissions from 143 in-use, predominantly line-haul locomotives were measured from two bridges near Tacoma, WA. Locomotive NOx emission factors were within levels reported in previous studies. While there is a 26% difference in certification standards, the real-world NOx measurements reported here found no statistical difference between mean emission factors for Tier 1 and Tier 2 locomotives. With the 2015 implementation of stringent Tier 4 emissions standards, remote sensing of NOx emissions by RSD would provide a useful, real-world, check on the expected in-use NOx reductions. Graphical abstract: